Catheter-Related Bloodstream Infection in Neonatal Intensive Care Unit: Prospective Surveillance Study - Maximiano, Cristiana; Cunha, Carla; Silva, Albina; Pereira, Almerinda (Gazeta Médica, 2021)
INTRODUCTION: Intravascular catheters are substantial in neonatal intensive care units (NICU). Monitoring infection rates is increasingly regarded as an important contributor to safe and high-quality health care. Our study aimed to determine the current incidence of catheter-related bloodstream infection (CRBSI) in a level III NICU, comparing with other reports and with a previous similar study performed in our NICU in 2011. METHODS: From January 2017 to December 2019 a prospective surveillance was undertaken in the NICU of Hospital de Braga. All newborns (NB) with a central catheter (CC) inserted in our NICU were considered. The microbiological diagnosis was performed by peripheral blood culture (BC) and the culture of the CC tip after removal. RESULTS: There were inserted a total of 404 CC, 138 umbilical catheters (UC), and 266 peripherally inserted central catheters (PICC). The average gestational age was 30.4 weeks (SD±3.89 w), mean birth weight of 1380.03 g (SD±742.68 g), with 76.03% of very low birth weight (VLBW). The mean length of CC use was 11.51 days (SD ±11.08 d). There were 95 positive CC tip cultures, 25 (26.32%) UC, and 70 (73.68%) PICC. From 41 BC collected, there were 9 positive (21.95%), 2 from NB with UC, and 7 from NB with PICC. In both cultures, coagulase-negative Staphylococci were the most common organism identified. CRBSI rate is 0.5%. The incidence density of catheter contamination was 20.43 per 1000 catheter-days. DISCUSSION: Comparing with the previous study from 2011, there is a significant improvement in the CRBSI rate, reflecting the efforts done to prevent infections. Our CRBSI rate and the infection microbiology were similar to other NICUs.